Advocating for The Once and Future Library - Singh, Daisy (Maine Policy Review, 2024)
Libraries deal with vital issues affecting society that need to be better articulated for greater public and legislator support. Problematic ebook business models are affecting copyright and privacy protections and contributing to inequity. Let’s sustain fundamental library tenets protections as libraries adapt to the future.